2019
DOI: 10.7759/cureus.5829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a University’s Institutional Review Board Based on Campus Feedback: A Cross-Sectional Study

Abstract: IntroductionMaintaining research ethics within a university and monitoring the campus Institutional Review Board (IRB) are essential responsibilities not to be taken lightly. IRBs occasionally need to be reviewed to see that they, as well as researchers, are adhering to rules and regulations on ethics through their submission and review procedures. Since there are no established measures for assessing IRB quality, it is unclear how to determine whether IRBs are achieving their intended aims. This study used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Like most other universities, the policy of Alfaisal University do not allow students to serve as PI on human subject research. Several COM students questioned the PI eligibility policy of the institution [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like most other universities, the policy of Alfaisal University do not allow students to serve as PI on human subject research. Several COM students questioned the PI eligibility policy of the institution [2].…”
Section: Discussionmentioning
confidence: 99%
“…Research remains an essential pillar of most academic institutions despite the encountered challenges [1]. One of the challenges is determining the eligibility of a student to serve as a principal investigator (PI) on a study involving human subjects [2]. Another challenge is the need for more physicians to design and direct clinical research projects [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have been considered a cumbersome process. In a survey by Rajab et al (2019) [39], participants reported that the review process is tedious and time-consuming and the guidelines are ambiguous. On average, the IRBs review 40 protocols of clinical trials annually, and the duration of each meeting is around 45-120 min.…”
Section: Knowledge Of the Existence And Significance Of Irb Statementsmentioning
confidence: 99%